4. \( \begin{aligned} 3 x+2 y & =12 \\ 2 x-4 y & =0\end{aligned} \)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
The Deep Dive
To solve this system of equations, we can use the substitution or elimination method. Let's use the elimination method here. First, align both equations: 1. \( 3x + 2y = 12 \) (Equation 1) 2. \( 2x - 4y = 0 \) (Equation 2) To eliminate \(y\), we can multiply Equation 1 by 2 and Equation 2 by 1: - \( 2(3x + 2y) = 2(12) \) → \( 6x + 4y = 24 \) (Equation 3) - \( 1(2x - 4y) = 1(0) \) → \( 2x - 4y = 0 \) (Equation 2 remains unchanged) Now, add Equation 3 and Equation 2: \[ (6x + 4y) + (2x - 4y) = 24 + 0 \] \[ 6x + 2x + 4y - 4y = 24 \] \[ 8x = 24 \] \[ x = 3 \] Now substitute \(x = 3\) back into Equation 1 to find \(y\): \[ 3(3) + 2y = 12 \] \[ 9 + 2y = 12 \] \[ 2y = 3 \] \[ y = \frac{3}{2} \] The solution to the system of equations is \(x = 3\) and \(y = \frac{3}{2}\).